Recommendations of physical activity and rest in a Colombian prenatal control program - Ruiz-Rodríguez, Myriam; Sánchez-Martínez, Yuri; Ramírez-Muñoz, Paula Camila; Camargo-Lemos, Diana Marina (Revista de Saúde Pública, 2019)
OBJECTIVE: To determine the frequency of the registry of physical activity and rest recommendations made to pregnant women and to explore their associated factors in a prenatal care program of primary care public institutions in Bucaramanga, Colombia. METHODS: An observational study was conducted. The sampling frame consisted of the medical records of the pregnant women who attended at least one prenatal care program between January 1 and December 31, 2012 (n = 2.932), in 21 primary care health centers. We analyzed sociodemographic variables, prenatal and clinical antecedents, and information related to health personnel and the organization of health centers as possible factors associated with the recommendations of physical activity and rest recorded in the clinical history. Logistic regression models were applied to explore associations with α = 0.10. RESULTS: There was a frequency of 26.1% of PA recommendations and 3.6% of rest recommendation on record, issued by nutrition (97.3%) and medical (86.7%) professionals, respectively. The factors associated with the registration of physical activity recommendations were: being nulliparous pregnant (OR = 1.7), attending more than four Prenatal Care Attention Programs (OR = 2.2), having high or medium obstetric risk in the first prenatal care program (OR = 0.6), and being attended in the western (OR = 0.5) and eastern (OR = 0.2) administrative areas health centers. CONCLUSIONS: The low frequency of physical activity recommendations found in the records makes it necessary to reinforce the management strategies of health centers and strengthen the monitoring and accompaniment to comply with the care protocols. In addition, it is necessary to train health teams on the benefits of physical activity and their proper prescription, considering the multiple benefits derived from their practice on the maternal-fetal health.